Reduced red and processed meat consumption is associated with lower diet costs in US households: a national analysis of protein substitutions - Dania Orta-Aleman; Andrew L Thorne-Lyman; Roni Neff; Julia Wolfson; Laura E Caulfield (Cambridge University Press, 2024)
Abstract Objective: To examine the association between red and processed meat consumption and total food expenditures in US households and explore whether households could reduce food costs by substituting these meats with other protein sources such as poultry, seafood, eggs and plant proteins. Design: Cross-sectional study using data from the National Household Food Acquisition and Purchase Survey (FoodAPS). Using adult male equivalents (AME) for standardisation, we categorised red and processed meat purchases into quintiles. We used generalised linear models to explore the association between red or processed meat consumption and food expenditures and the cost effect of substituting meat with other proteins. Setting: United States. Participants: Data from 4739 households with valid acquisition information from FoodAPS, a stratified multistage probability sample of US households. Results: Higher red and processed meat consumption were both significantly associated with higher total weekly food expenditures, particularly among households with low income. Substituting red or processed meat with poultry, eggs or plant proteins did not significantly affect overall food expenditures, whereas replacing meat with seafood, especially varieties high in n-3 fatty acids, led to increased costs. Conclusions: Reducing red and processed meat consumption could offer savings for households, particularly those with low income. Although substitutions with seafood high in n-3 could increase expenses, alternative protein sources like poultry and plant proteins may serve as cost-neutral replacements. Public health strategies should emphasise dietary shifts' economic, health and environmental benefits and aim to make nutritious yet affordable protein sources more accessible.